Stereotype and abnormal behaviour in Macaca fascicularis captive: Towards good environmental enrichment for its sustainability - Nasution, Erie; Al-Hakim, Rosyid; Rukayah, Siti (Lembaga Pengembangan Kinerja Dosen, 2022)
Stereotypes and abnormal behaviour (SAB) exhibited by long-tailed macaques (LTMs) have attracted the attention of behavioural study, although caused by many factors. Mostly found in captivity, it can also occur in the natural environment. This study aims to review several scientific articles on SAB in LTMs, as well as for environmental enrichment conditions. This study used a web-based survey to collect all scientific publications related to SAB in LTMs with a statistical correlation test to determine the cost of individuals' needs as an animal model for the research and the regression test to determine the effects of the number of individuals observed, as well as SAB types in LTMs. This study used two variables: the number of individuals and SAB types and sorted by rank. The statistical correlation result shows that the cost of individuals' needs as an animal model for the research and publication's year is positive correlate. The regression test result shows that the total number of individuals observed is significantly different (p-value<0.05, one-tailed) between SAB types. The primary goal of stimulating environmental enrichment is to give pleasant options for animals based on the treatment object in the study supplied while emphasising animal welfare and promoting research effectiveness.